Customer perceptions about family firms and their effects on customer behaviors (Journal of Small Business Strategy (archive only), 2021)
The current is an exploratory project exploring the associations and impressions evoked by the term “family-owned business” (FOBs) and how these impressions affect intentions to buy from a family firm. Four studies were conducted to assess the perceptions about family firms. Based on signaling theory and the theory of reason action, it was predicted that the family nature of firms would act as a signal that consumers will use to determine perceptions, attitudes towards family firms, and intentions to buy from family firms. Results indicate that, in general, participants had positive perceptions about organizational values and neutral perceptions about products and services offered by family firms. As suggested by the Theory of Reasoned Action, these perceptions affected attitudes and intentions towards FOBs. Implications for theory and practice are discussed.